Comparison Of Financial Performance With Solvency And Profitability Ratio Between Building Construction Sub-Industry And Property & Real Estate Sub-Sector On The Indonesia Stock Exchange - Lestari, Lestari; Erdiana, Atty (Doctoral Program of Social Science Pasundan University, 2025)
This study examines the comparison of performance between companies in the building construction sub-sector and the property & real estate sub-sector on the Indonesia Stock Exchange with the measuring variables being Debt to Assets Ratio (DAR), Debt equity ratio (DER), Return on Investment (ROI) and Return on equity (ROE). The general objective of this study is to identify financial performance based on the DAR, DER, ROI and ROE ratios.construction sub-sector companies and property & real estate sub-sectors on the Indonesia Stock Exchange. These ratios are used as a measure of financial performance of the 2 industry groups so that it can be seen whether the 2 industry groups have relatively the same or different performance. While the specific objective of this study is to find out which assets between debt or equity (own capital) provide the largest contribution in contributing to the company's profits. This study uses a purposive sampling method, considering that the companies studied are companies that publish financial reports in 2024 at least Q3. Meanwhile, to measure the comparison/differences between the two industrial sub-sectors, the Independent Sample T Test analysis technique is used. The results of this study indicate that there is no difference in financial performance between the building construction sub-sector companies and the property & real estate sub-sector companies.